Implementation of Land Registration Transformation Electronic Land Services at the Land Office of Tegal Regency - Ulfah, Ulu Maeni; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The implementation of the transformation of land certificates from analog certificates to electronic certificates is carried out in stages through a media transfer process. The consideration for issuing the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 1 of 2021 concerning Electronic Certificates is to realize improved land services in order to improve public services to the community and indicators of ease of doing business, which are supported by information and communication technology by implementing electronic-based land services. The digitization of land certificates in Indonesia occurs when there is a new registration application and then the electronic land certificate process or media transfer from analog certificates to electronic land certificates is carried out, or due to something such as the practice of land buying and selling processes, changes in ownership status and others. Although there are no sanctions in the Regulation of the Minister of ATR/BPN Number 1 of 2021 concerning Electronic Certificates, for parties who are reluctant to digitize land certificates, it is undeniable that the digitization of land certificates in Indonesia will continue. Therefore, the ATR/BPN Office of Tegal Regency as the agency that technically oversees the land sector can prepare in terms of human resources (HR) and quality by prioritizing the principles of caution and accuracy.Keywords: Certificate; Digitalization; Electronic; Media.